Coir Fiber Reinforced Polypropylene Composites: Eco-friendly Byproducts (Journal of Environmental Science and Natural Resources, 2017)
Coir fiber (CF) reinforced polypropylene (PP) composites were fabricated using an extruder machine. The fiber contents were varied 5 to 20% and physico-mechanical properties as well as bio-degradability were also tested. Ultimate tensile strength and flexural strength decreases with the increases of percentages of fiber addition. Lowest percentage elongation is observed at 20% CF+PP composite which are rigid in nature. Leeb rebound hardness also decreases with the increase of percentage of raw fiber addition. The bio-degradation of different percentage of CF and PP composites in soil and saline water increased with increase of coir fiber content. Thus, it showed that higher percentage of coir fiber was produced more biodegradable and eco-friendly byproducts. However, higher percentages of coir fiber decrease the mechanical properties. A moderate percentage of coir fiber i.e. 15% CF +PP showed the good mechanical properties as well as considerable amount of bio-degradability in soil and saline water.J. Environ. Sci. & Natural Resources, 10(1): 61-64 2017